2020
DOI: 10.1016/j.psj.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mathematical and comparative slaughter methodologies for determination of heat production and energy retention in broilers

Abstract: Understanding factors affecting ME availability for productive processes is an important step in optimal feed formulation. This study compared a modelling methodology with the comparative slaughter technique ( CST ) to estimate energy partitioning to heat production and energy retention ( RE ) and to investigate differences in heat dissipation. At hatch, 50 broilers were randomly allocated in one of 4 pens equipped with a precision feeding station. From day 14 to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
1
0
2
Order By: Relevance
“…The results could have been confounded by dietary factors, as the diet was switched at week 23 (from a grower to peak layer diet). However, it was previously concluded that diet composition did not affect the heat increment feeding in broilers ( van der Klein et al., 2020 ). In immature feed restricted birds, it is possible that part of the increase in ME intake will directly partition to gain, predominantly toward lean tissues.…”
Section: Resultsmentioning
confidence: 98%
“…The results could have been confounded by dietary factors, as the diet was switched at week 23 (from a grower to peak layer diet). However, it was previously concluded that diet composition did not affect the heat increment feeding in broilers ( van der Klein et al., 2020 ). In immature feed restricted birds, it is possible that part of the increase in ME intake will directly partition to gain, predominantly toward lean tissues.…”
Section: Resultsmentioning
confidence: 98%
“…As diferenças de resultados podem estar associadas a espécies e linhagens diferentes (Silva et al, 2012), consequentemente suas exigências também serão devidas suas características metabólicas particulares. Além disso, diversos fatores ambientais podem afetar nessa divergência de estimativas de exigência de bruta para mantença (PBm), como: temperatura (Aksit et al, 2013), empenamento (KIM et al, 2016, nível de consumo (Mauricio et al, 2018), genética (Wang et al, 2022), técnica do abate comparativo (Klein et al, 2020) e balanço de nitrogênio (Jordão Filho et al, 2011;Silva et al, 2004a).…”
Section: Resultados E Discussõesunclassified

Modelo para predizer as exigências em proteína bruta para codornas japonesa em postura

De Diniella dos Santos Bourdon,
Vargas Gonçalves Vieira,
Guilherme Perazzo Costa
et al. 2023
PRW
“…Além disso, a RNA tem sido utilizada para avaliar a depleção de linfócitos na bolsa de Fabricius e no timo (3,11,12) . Outros modelos matemáticos e sistemas de inteligência também têm sido desenvolvidos para possibilitar o gerenciamento de dados em diversas áreas da cadeia produtiva avícola (13)(14)(15)(16) .…”
Section: Introductionunclassified